Failure to get Admissions in a Discipline of their own Choice: Voices of Dejected Students - Naeem Akhtar Rana; Naeem Tuba (Journal of Education and Educational Development, 2020)
Attaining a professional engineering degree is a dream of many pre-engineering intermediate students in Pakistan. Several students face scarcity of resources to accomplish and enliven their dreams of getting admission into an engineering institute, which results in great hardships and turmoil for them. The literature reveals that quantitative work in this area has been done to some extent, which restricts the comprehension of deeper understanding, profound feelings, perceptions, personal meanings, effects and experiences surrounding this dilemma at the time of rejection. This study has tried to ferret out the experiences of the students who could not get admission in the field of their own interest and went through the phase of uncertainty concerning their future. The research is grounded in the tradition of hermeneutic phenomenology as guided by Heidegger (1962), Gadamer (1960/2003), Casey (1993) and Levinas (1961/2004). By calling forth the philosophical and methodological tenets of this approach, the endeavor was to uncover the lived experiences of the students at the time of failure as well as how they felt about their future. A group of five students from the University of Karachi (Department of Statistics), who could not qualify in the Entrance test of a well renowned Engineering University in Karachi and later joined BS program in Actuarial Sciences, were interviewed for this research. The insights of the study reflect that lack of opportunities and failure result in a great set back for the students and harbor negative feelings in them towards education and its system. The study recommends the need to establish new public sector universities to fulfill the needs of the students to achieve their targets and simultaneously to groom them as an asset for the country.
Keywords: engineering; hermeneutic phenomenology; professional aspirations; tertiary level